Actividades lúdicas para estimular la motricidad fina en niños de educación inicial - Garcia Mora, Elizabeth Carolina (2024)
It is taken into account that recreational activities help to promote the main skills that human beings must develop during their first years, allowing them to fully develop in other areas that are necessary for the management of daily activities or for the resolution of conflicts. . Therefore, this research work focuses on exposing how recreational activities help to stimulate fine motor skills in children in early education, taking into account the opinions of other authors who serve as a reference to further investigate the problem. That is why the non-experimental research design and the mixed research approach will be used, as well as the type of documentary and field research. For this reason, we were allowed to observe more closely the composition of the recreational activities and how they help to stimulate fine motor skills, for which in-depth investigations were carried out that yielded a certain budget to carry out said investigation. The technique and instruments were observation, survey and questionnaire to obtain better results. It should be noted that the research method to be used was the analytical-synthetic method, which helped us observe the factors that cause the problem to later give a general verdict of the study, allowing us to determine how recreational activities are of great help in obtaining of these skills in the human being, which are fundamental to develop other more complex skills.